South Africa’s Correctional System Security Dynamics - Motlalekgosi , Puleng (Research Aspects in Arts and Social Studies Vol. 2, 2022)
Security within prisons is one function that forms the core business and is a critical success factor of correctional systems across the world. This analytical essay discussed security dynamics within the prisons in South Africa. It argued that an effective correctional system is dependent on an understanding of security dynamics including but not limited to the functions of the custody, searching as a security function, methods of searching, inmates’ control procedures, treatment function of custody and the use of force in prisons.